FILSAFAT PENDIDIKAN OTOMOTIF DALAM ERA DIGITAL: SEBUAH ANALISIS TENTANG PERUBAHAN KONSEP BELAJAR DAN MENGAJAR DALAM PENDIDIKAN MULTIVARIAT - Meiyaldi Eka Putra; Refdinal Refdinal; Rijal Abdullah; Jonni Mardizal; Ambiyar Ambiyar (Smart Education, 2025)
Abstract: The rapid development of digital technology has brought significant transformation to the philosophy of automotive education, particularly in its traditional learning and teaching approaches that previously relied on manual skills. This study aims to analyze the shift in automotive education from the perspective of multivariate educational philosophy, which integrates technical competencies, digital literacy, problem-solving abilities, and an understanding of electronic vehicle systems. Using a qualitative approach, data were collected through in-depth interviews and observations involving automotive teachers, workshop instructors, program coordinators, industry technicians, and students. The findings reveal that digital tools—such as vehicle scanners, simulation software, animated videos, and e-learning modules—not only enhance learning methods but also shift the learning paradigm toward more analytical and data-driven processes. The role of teachers has also evolved significantly, from mere transmitters of information to facilitators, mentors, and digital analysts. The integration of industry technology into classroom and workshop learning increases students’ job readiness and reduces the skills gap between vocational schools and professional workshops. Therefore, automotive education in the digital era requires a philosophical reconstruction to align with multivariate competence demands, curriculum relevance, and the technological needs of the modern automotive industry. Keyword: educational philosoph; automotive education; digital era; multivariate learning; industrial technology integration Abstrak: Perkembangan teknologi digital telah membawa perubahan mendasar terhadap filsafat pendidikan otomotif, terutama dalam cara belajar dan mengajar yang sebelumnya berpusat pada keterampilan manual. Penelitian ini bertujuan menganalisis transformasi konsep pendidikan otomotif dalam perspektif filsafat pendidikan multivariat, yang menekankan keterpaduan antara kompetensi teknis, literasi digital, pemecahan masalah, serta pemahaman sistem elektronik kendaraan modern. Menggunakan pendekatan kualitatif, data diperoleh melalui wawancara mendalam dan observasi pada guru otomotif, instruktur bengkel, kepala program keahlian, teknisi industri, serta siswa. Hasil penelitian menunjukkan bahwa teknologi digital, seperti scanner kendaraan, software simulasi, video animasi, dan modul e-learning, tidak hanya memodifikasi metode pembelajaran, tetapi juga menggeser paradigma belajar menuju model yang lebih analitis dan berbasis data. Peran guru turut mengalami perubahan signifikan, dari penyampai informasi menjadi fasilitator, mentor, dan analis digital. Integrasi teknologi industri dalam pembelajaran terbukti meningkatkan kesiapan kerja siswa dan mengurangi kesenjangan keterampilan antara sekolah dan bengkel modern. Dengan demikian, pendidikan otomotif dalam era digital memerlukan rekonstruksi filosofis agar mampu menjawab tuntutan kompetensi multivariat, relevansi kurikulum, serta kebutuhan industri otomotif berbasis teknologi. Kata kunci: filsafat pendidikan; pendidikan otomotif; era digital; pembelajaran multivariat; teknologi industri